2022
DOI: 10.3390/cells11030516
|View full text |Cite
|
Sign up to set email alerts
|

Neurodegenerative Disease-Associated TDP-43 Fragments Are Extracellularly Secreted with CASA Complex Proteins

Abstract: Extracellular vesicles (EVs) play a central role in neurodegenerative diseases (NDs) since they may either spread the pathology or contribute to the intracellular protein quality control (PQC) system for the cellular clearance of NDs-associated proteins. Here, we investigated the crosstalk between large (LVs) and small (SVs) EVs and PQC in the disposal of TDP-43 and its FTLD and ALS-associated C-terminal fragments (TDP-35 and TDP-25). By taking advantage of neuronal cells (NSC-34 cells), we demonstrated that b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…Dr. D'Agostino showed that a DNA base‐excision repair protein, that is, APE1, modulates the secretion of EV‐RNA (Mangiapane et al., 2021), providing evidence that a functional base‐excision repair protein is delivered through exosomes in response to genotoxic stresses. Dr. Elena Casarotto used microRNA analysis to investigate whether and how the protein quality control system (PQC) can affect not only the secretion of proteins into large and small EVs (Casarotto et al., 2022), but also the EV microRNA content, especially in the context of neurodegenerative diseases, where the PQC is usually impaired.…”
Section: Quantitatevs Workhop Points Of Discussion and Related Raised...mentioning
confidence: 99%
“…Dr. D'Agostino showed that a DNA base‐excision repair protein, that is, APE1, modulates the secretion of EV‐RNA (Mangiapane et al., 2021), providing evidence that a functional base‐excision repair protein is delivered through exosomes in response to genotoxic stresses. Dr. Elena Casarotto used microRNA analysis to investigate whether and how the protein quality control system (PQC) can affect not only the secretion of proteins into large and small EVs (Casarotto et al., 2022), but also the EV microRNA content, especially in the context of neurodegenerative diseases, where the PQC is usually impaired.…”
Section: Quantitatevs Workhop Points Of Discussion and Related Raised...mentioning
confidence: 99%
“…The CASA complex may utilize alternative pathways for substrates disposal, which are based on CASA complex secretion into the extracellular environment [ 135 ]. It has been postulated that CASA complex secretion into extracellular vesicles might represent an alternative attempt of cells to clear proteotoxic and aggregating substrates when the intracellular degradative pathways are impaired [ 136 ]. In support of this notion, the toxic fragments of TARDBP/TDP-43 (TAR DNA binding protein) associated with amyotrophic lateral sclerosis (ALS) have been detected in extracellular vesicles containing CASA complex members and their secretion increased upon combined UPS and autophagy blockage [ 136 ].…”
Section: The Role Of the Casa Complex In Extracellular Secretionmentioning
confidence: 99%
“…TDP-43 has a prionlike structure at its C-terminal domain that enables it to propagate to cultured cells in an EV-mediated mechanism. 9,10,49 Further evidence of the role of EVs in TDP-43 propagation revealed the ability of extracellular exosomes with TDP-43 aggregates to transmit intercellularly and exhibit seeding properties. 50 EVs may also contribute to the propagation of nucleic acids and neuroinflammation.…”
Section: Referencesmentioning
confidence: 99%
“…Given that TDP‐43 aggregates are found in damaged cells of ALS patients, elucidating the mechanism of accumulation is paramount. TDP‐43 has a prion‐like structure at its C‐terminal domain that enables it to propagate to cultured cells in an EV‐mediated mechanism 9,10,49 . Further evidence of the role of EVs in TDP‐43 propagation revealed the ability of extracellular exosomes with TDP‐43 aggregates to transmit intercellularly and exhibit seeding properties 50 …”
Section: The Consequence Of Ev Propagation Of Als Pathology and Their...mentioning
confidence: 99%